1998
DOI: 10.1161/01.cir.98.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Direct In Vivo Visualization of Intravascular Destruction of Microbubbles by Ultrasound and its Local Effects on Tissue

Abstract: Background-Our aim was to observe ultrasound-induced intravascular microbubble destruction in vivo and to characterize any resultant bioeffects. Methods and Results-Intravital microscopy was used to visualize the spinotrapezius muscle in 15 rats during ultrasound delivery. Microbubble destruction during ultrasound exposure caused rupture of Յ7-m microvessels (mostly capillaries) and the production of nonviable cells in adjacent tissue. The number of microvessels ruptured and cells damaged correlated linearly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
270
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(283 citation statements)
references
References 11 publications
10
270
1
2
Order By: Relevance
“…30 Some collateral lesions exhibit red blood cell extravasations and even rupture of microvessels in the exposed area. 34,41 In vivo studies of ultrasound-microbubble-mediated transfection have shown apoptosis in 17% of exposed cells in the rabbit brain 42 and less than 1% of all treated skeletal muscle of rats. 43 Amabile et al 44 reported apoptosis in 26% of vascular endothelial cells following endovascular ultrasound delivery of adenovirus-expressing gene.…”
Section: Discussionmentioning
confidence: 99%
“…30 Some collateral lesions exhibit red blood cell extravasations and even rupture of microvessels in the exposed area. 34,41 In vivo studies of ultrasound-microbubble-mediated transfection have shown apoptosis in 17% of exposed cells in the rabbit brain 42 and less than 1% of all treated skeletal muscle of rats. 43 Amabile et al 44 reported apoptosis in 26% of vascular endothelial cells following endovascular ultrasound delivery of adenovirus-expressing gene.…”
Section: Discussionmentioning
confidence: 99%
“…Insonation of microbubbles at a sufficiently high concentration or with a sufficiently high mechanical stress (low frequency, high acoustic pressure) results in changes in the permeability of capillary wall, with resulting extravasation of particles into the interstitial space [9,10]. In such cases, convective transport can result in transport of drugs or particles over distances on the order of tens of microns from the vessel wall and therefore far from the location of the microbubble oscillation.…”
Section: Changes In Tissue/vascular Transport Propertiesmentioning
confidence: 99%
“…These vascular alterations included changes in permeability (i.e., leakage of Evans blue dye) and integrity (i.e., petechial hemorrhages), focal endothelial cell and myocyte loss and necrosis, inflammation and replacement fibrosis (Hwang et al 2005;Li et al 2004;Miller andGies 1998,2000;Miller et al 2004Miller et al ,2005Miller and Quddus 2000;Skyba et al 1998). Arrhythmogenic changes included premature ventricular contractions in healthy adult human beings during triggered second-harmonic imaging of a CA for myocardial perfusion (van Der Wouw et al 2000); supraventricular tachycardia or nonsustained ventricular tachycardia in patients at risk for syncope, supraventricular tachycardia or ventricular tachycardia after IV administration of per-fluorocarbon-exposed sonicated dextrose albumin microbubbles (PESDA), exposure to therapeutic transthoracic low-frequency US (Chapman et al 2005) and cardiac arrhythmogenesis in a rat model (Zachary et al 2002).…”
Section: Introduction and Literaturementioning
confidence: 99%